Quadri di un’esposizione: un’analisi del film Brama di vivere - Alberto Boschi (Annali Online dell'Università di Ferrara. Sezione Lettere, 2023)
Starring Kirk Douglas as Vincent Van Gogh, Lust for Life (directed by Vincente Minnelli, 1956) is one of the most celebrated Hollywood biopics focusing on the life of a visual artist. This essay aims to offer further food for thought thanks to a detailed and systematic scrutiny of the film, that nevertheless takes into consideration the most significant critical reviews and analyses from the previous decades. Among the main topics here dealt with, we can mention the relationship between Lust for Life and Irving Stone’s novel from which the script was adapted, and the complex system elaborated by Minnelli to include Van Gogh’s paintings in his film.